Common data elements for epilepsy mobile health systems. (31st March 2018) - Goldenholz, Daniel M.; Moss, Robert; Jost, David A.; Crone, Nathan E.; Krauss, Gregory; Picard, Rosalind; Caborni, Chiara; Cavazos, Jose E.; Hixson, John; Loddenkemper, Tobias; Salazar, Tracy Dixon; Lubbers, Laura; et al.
Summary: Objective: Common data elements (CDEs) are currently unavailable for mobile health (mHealth) in epilepsy devices and related applications. As a result, despite expansive growth of new digital services for people with epilepsy, information collected is often not interoperable or directly comparable. We aim to correct this problem through development of industry‐wide standards for mHealth epilepsy data. Methods: Using a group of stakeholders from industry, academia, and patient advocacy organizations, we offer a consensus statement for the elements that may facilitate communication among different systems. Results: A consensus statement is presented for epilepsy mHealth CDEs. Significance: Although it is not exclusive, we believe that the use of a minimal common information denominator, specifically these CDEs, will promote innovation, accelerate scientific discovery, and enhance clinical usage across applications and devices in the epilepsy mHealth space. As a consequence, people with epilepsy will have greater flexibility and ultimately more powerful tools to improve their lives.